Positive Parenting Training for Early Childhood by the Stages of Development at TPA Melati Dharma Wanita Persatuan UM - Rezka Arina Rahma; Sucipto Sucipto; Kukuh Raharjo; R. Anggia Listyaningrum (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Children receive their first education in a family. However, not many families understand the knowledge of parenting by paying attention to the stage of development. In general, parents who live in cities are more likely to entrust their care to the Child Care Center (TPA) while the parents are working in the hope that their children will be able to get proper attention from their parents. TPA, engaged in early childhood education, has demanded or is obliged to provide education and guidance to children according to their rights and developmental aspects. However, in reality, not all TPA understand positive parenting that pays attention to the stage of child development. This results in the non-fulfillment of children's rights, such as being privileged and always being considered. This condition is a bad thing because there are risks that must be borne by the child himself, such as the child is not confident, does not trust others, is afraid to meet other people, and so on. The implementation of this community service uses a share and care approach. Share has understanding through sharing experiences in overcoming problems of early childhood care and how to understand each child's development. Care is a trip and trick providing good communication techniques for children and fun discipline techniques for children. The methods used are identification and socialization of activities, training, mentoring, discussion, and evaluation. The results of this activity are increased childcare skills for parents and caregivers at TPA Melati, increased communication skills with early childhood, and fostering discipline in children according to their stages of development.